Synthesis of Adipic Acid Catalyzed by Sodium Hypochlorite under Ultrasound Irradiation - Lin, Zhi-Ping; Li, Ji-Tai (Asian Journal of Chemistry, 2012)
Adipic acid was synthesized from cyclohexanol oxidized by sodium hypochlorite in 94 % yield within 4 h under ultrasound irradiation.